2017
DOI: 10.1038/s41598-017-10175-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NCAN as a candidate gene for developmental dyslexia

Abstract: A whole-genome linkage analysis in a Finnish pedigree of eight cases with developmental dyslexia (DD) revealed several regions shared by the affected individuals. Analysis of coding variants from two affected individuals identified rs146011974G > A (Ala1039Thr), a rare variant within the NCAN gene co-segregating with DD in the pedigree. This variant prompted us to consider this gene as a putative candidate for DD. The RNA expression pattern of the NCAN gene in human tissues was highly correlated (R > 0.8) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In addition, KIAA0319 was listed in the top 300 genes reported to be significantly associated with general cognitive ability in gene‐based analyses conducted for a large sample ( N = 280, 360; Davies et al., ). A number of other genes and types of variants such as copy number variations (Pagnamenta et al., ; Poelmans et al., ; Veerappa, Saldanha, Padakannaya, & Ramachandra, ) and rare coding mutations in CCDC136/FLNC, NCAN and CEP63 in isolated families (Adams et al., ; Einarsdottir et al., , ) have been implicated in dyslexia. For recent detailed reviews on the genetics of dyslexia and language disorders, see (Carrion‐Castillo et al., ; Graham & Fisher, ; Kere, ; Newbury et al., ; Paracchini et al., ).…”
Section: Developmental Dyslexiamentioning
confidence: 99%
“…In addition, KIAA0319 was listed in the top 300 genes reported to be significantly associated with general cognitive ability in gene‐based analyses conducted for a large sample ( N = 280, 360; Davies et al., ). A number of other genes and types of variants such as copy number variations (Pagnamenta et al., ; Poelmans et al., ; Veerappa, Saldanha, Padakannaya, & Ramachandra, ) and rare coding mutations in CCDC136/FLNC, NCAN and CEP63 in isolated families (Adams et al., ; Einarsdottir et al., , ) have been implicated in dyslexia. For recent detailed reviews on the genetics of dyslexia and language disorders, see (Carrion‐Castillo et al., ; Graham & Fisher, ; Kere, ; Newbury et al., ; Paracchini et al., ).…”
Section: Developmental Dyslexiamentioning
confidence: 99%
“…For example, whole-exome sequencing (WES) in an extended Swedish family identified a two-base mutation (chr3:123264558-9, hg19), which resulted in an amino acid change (p.R229L) within the CEP63 gene, partially cosegregating with dyslexia: seven out of ten of the affected individuals were carriers of the risk variant (Einarsdottir et al 2015 ). Another study that reported ten putatively linked loci in a Finnish family used whole-exome and whole-genome sequencing (WGS) in two critical individuals of the family to identify a rare non-synonymous variant within the NCAN gene, on chromosome 19p13.11 (maximum NPL = 1.36) (Einarsdottir et al 2017 ). The variant was present in seven out of eight affected individuals and one out of four unaffected family members (Einarsdottir et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study that reported ten putatively linked loci in a Finnish family used whole-exome and whole-genome sequencing (WGS) in two critical individuals of the family to identify a rare non-synonymous variant within the NCAN gene, on chromosome 19p13.11 (maximum NPL = 1.36) (Einarsdottir et al 2017 ). The variant was present in seven out of eight affected individuals and one out of four unaffected family members (Einarsdottir et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurocan is a CSPG that is a prominent organizer of PNNs in the neocortex. Genetic studies in humans have identified Neurocan as a potential risk factor for schizophrenia, bipolar disorder ( Muhleisen et al, 2012 ; Schultz et al, 2014 ; Wang et al, 2016 ), and dyslexia ( Einarsdottir et al, 2017 ). Our interest in mechanisms regulating spine density in the developing cortex led us to investigate molecules that may mediate the reduction of spine remodeling that occurs with maturation.…”
Section: Introductionmentioning
confidence: 99%